ANALISIS PERLINDUNGAN WANITA DALAM UNDANG-UNDANG PERKAWINAN TERKAIT PASAL PEMERKOSAAN DALAM PERNIKAHAN YANG SAH - Ikramina Yustika Barito (Journal of Law ( Jurnal Ilmu Hukum ), 2021)
AbstractMarriage is a relationship in an arrangement of living tissue and is a natural human community that has been reduced to be shown to perpetuate offspring which will later form a family. Marriage is a covenant or agreement that is very serious, strong, contains transcendental values, carried out consciously by men and women to form a family whose implementation is based on willingness and agreement between the two parties. This study uses normative juridical research also called doctrinal law research. "In this type of legal research, it is conceptualized as what is written in the regulation of the law (law in books) or the law is conceptualized as a valid rule or norm. Marital rape is included in sexual violence as mentioned in Article 8 where the perpetrators and victims are included in the scope of the household. So that article 8 of Law No. 23 of 2004 concerning the Elimination of Domestic Violence can be used as a legal basis if followed up through legal channels. Marital rape in sexual violence mentioned in article 480 of the Criminal Code Code can be charged with 12 years imprisonment.